Role of MRI in delineation of internal derangement of knee in trauma patients - Gupta, R; Chandel, NS; Vyas, MM (International Journal of Medical Research and Review, 2015)
Introduction: Knee joint is one of the most commonly injured joints, as an isolated injury or a frequent component in a multiple trauma patient. Knee joint injury is a significant cause of morbidity in young and active individuals especially amongst sports person, laborers, soldiers and military recruits. Multiple imaging modalities are currently being used to evaluate various pathological conditions of the knee including conventional radiography, CT scan, sonography , nuclear medicine and MR Imaging. Multi planar imaging and excellent soft tissue contrast has made the MRI an ideal modality for imaging of complex anatomy of knee joint in trauma patient. Objective: To study the diagnostic accuracy & efficacy of MRI in evaluation of internal derangement of knee joint in trauma patient. Material & Method: 44 cases with history of trauma were evaluated by Siemens magnetom vision plus 1.5 tesla MRI machine. Results: Mean age of patient - 32.2 years. Count of male patients exceeded the count of female patients. ACL injury was observed in 81.8%, PCL injury in 6.8%, MCl in 11.3%, LCL in 2.3%, medial meniscal tear in 45.5%, joint effusion in 95%. Conclusion: MRI emerged as a front line investigation for the assessment of internal derangement of knee joint in trauma patient.